2014
DOI: 10.1111/bjd.13130
|View full text |Cite
|
Sign up to set email alerts
|

Latent tuberculosis infection in patients with chronic plaque psoriasis who are candidates for biological therapy

Abstract: The prevalence of LTBI in patients with psoriasis is similar to that in patients with Crohn disease or RA and in healthcare workers. Prophylaxis with isoniazid is effective in preventing tuberculosis reactivation in patients with LTBI receiving biological therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…1 There is an increasing proportion of cases among immigrants, which reached 67Á5% of total confirmed TB cases in northern Italian regions. 2 There are relatively scarce data regarding the prevalence of latent TB infection (LTBI) in patients with psoriasis, [3][4][5][6][7] and the nationwide prevalence of patients with LTBI with moderate-to-severe psoriasis, candidate to systemic treatment has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 There is an increasing proportion of cases among immigrants, which reached 67Á5% of total confirmed TB cases in northern Italian regions. 2 There are relatively scarce data regarding the prevalence of latent TB infection (LTBI) in patients with psoriasis, [3][4][5][6][7] and the nationwide prevalence of patients with LTBI with moderate-to-severe psoriasis, candidate to systemic treatment has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies reported a prevalence rate of LTBI in patients with psoriasis of 5-22% in Italy, [3][4][5][6][7]23 11% in Taiwan 24 and 20-29% in Spain, which is a high-prevalence country for TB. 25,26 LTBI was diagnosed by TST in 13Á4% of patients with rheumatic diseases (rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis) undergoing treatment with infliximab in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…TB reactivation is frequently extrapulmonary and disseminated. In Italy the prevalence of latent TB in patients with moderate‐to‐severe psoriasis is 8.2% . Screening for LTBI is mandatory in patients who are candidate to biologics because of increased risk of LTBI reactivation, particularly with TNF‐α inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…In Italy the prevalence of latent TB in patients with moderate-to-severe psoriasis is 8.2%. 99 Screening for LTBI is mandatory in patients who are candidate to biologics because of increased risk of LTBI reactivation, particularly with TNF-a inhibitors. Although the risk of LTBI reactivation significantly differs among biologics, caution and vigilance are required for all biologics.…”
Section: Patients With Latent Tuberculosis Infectionmentioning
confidence: 99%
“…The incidence of tuberculosis is estimated in seven new cases per 100,000 people per year in Italy (http://www. In literature there are data on incidence of tuberculosis infection in psoriatic patients, but there are limited reports on efficacy of prophylaxis of LTBI in psoriatic patients treated for long-time with biological drugs Gisondi, Pezzolo, Lo Cascio, & Girolomoni, 2014;Laffitte et al, 2009). The use of biologics, particularly TNF-a inhibitors (infliximab, etanercept, and adalimumab) in the treatment of chronic inflammatory diseases can increase five times the risk of developing active tuberculosis in these patients by the fragmentation of TNF-dependent granulomas (Amerio et al, 2013;Gardam et al, 2003;Hernandez, Cetner, Jordan, Puangsuvan, & Robinson, 2009;Keane & Bresnihan, 2008;National Psoriasis Foundation, 2008;World Health Organization, 2015).…”
Section: Introductionmentioning
confidence: 99%